What to do with pragmatism?! Giovanni Maddalena’s attempt to complete Peirceian philosophy (KULT_online, 2017)
With The Philosophy of Gesture. Completing Pragmatists’ incomplete Revolution the Italian philosopher Giovanni Maddalena contributes to the increasingly importance of late ‘gesture research’ and transcends it at the same time. Following Charles Sanders Peirce and pragmatist philosophy, Maddalena’s ‘complete gesture’ turns into the tool for genuinely synthetic reasoning. Over 180 pages he manages to describe convincingly how non-analytic knowledge perfuses and determines all our doing.